Risk Evaluation of Musculoskeletal Disorders and Design of Lifting-carrying Facilities: Evaluasi Risiko Gangguan Otot Rangka dan Perancangan Fasilitas Angkat-Angkut - Agustina, Fitri; Ansori, Nachnul; Novianti, Trisita; Widiaswanti, Ernaning; Anggraeni, Ravida Ayu (Universitas Muhammadiyah Sidoarjo, 2023)
There are main activities of the worker in UD Askan such as splitting the fish, carrying, and lifting the tubs. Work activities are done manually and the production process continually undergoes. The frequency of activity (15 cycles) in a day causes the risk of fatigue, injury, and Musculoskeletal Disorders (MSDs). Evaluation of the work posture of four workers by Ovako Working Posture Analysis System (OWAS) and Job Strain Index (JSI) methods showed high risk in the process of lifting and carrying a tank. The previous posture caused the worker to bend forward, both legs standing or squatting with both knees, and walk by carrying a tub. The results recommend solving soonest due to the danger to the musculoskeletal. The recommendation shows that lifting methods are required and the design of lifting and transporting equipment is needed. The evaluation posture by OWAS show that the process of carrying a tank is 3 level (immediate repair because it is harmful to the musculoskeletal), and after improvement, it is 1 level (not harmful to the musculoskeletal). Then, JSI indicates any improvement from the 3 levels (posing a hazard) to level 1 (safe work).